The Consequences of chronic stereotype threat domain disidentification and abandonment. [article]. - Woodcock, Anna.
Stereotype threat impairs performance across many domains. Despite a wealth of research, the long-term consequences of chronic stereotype threat have received little empirical attention. Beyond the immediate impact on performance, the experience of chronic stereotype threat is hypothesized to lead to domain disidentification and eventual domain abandonment. Stereotype threat is 1 explanation why African Americans and Hispanic/Latino(as)s "leak" from each juncture of the academic scientific pipeline in disproportionately greater numbers than their White and Asian counterparts. Using structural equation modeling, we tested the stereotype threat-disidentification hypothesis across 3 academic years with a national longitudinal panel of undergraduate minority science students. Experience of stereotype threat was associated with scientific career. We discuss findings in terms of understanding chronic stereotype threat. - (from the authors).
Keywords: Hernandez, Paul R; Estrada, Mica; Stereotype threat; Academic identification; Structural equation modelling; Longitudinal research; Scale validation